STOLF SUPER PLOW IN TANDEM WITH 9 DISCS: Super arado Stolf em Tandem para tratores de alta potência - Stolf, Rubismar (2025)
The objective was to design a plow model with a working width of 3000 mm, nonexistent in the agricultural market: From the 1960s, with the transfer of the capital of Brazil to the central plateau, investment in the Midwest began, giving rise to a strong agriculture of large agricultural properties. This fact encouraged harrow designs with large working widths. However, there was no progress in the design of plows; on the contrary, their use was reduced by the replacement with harrows. Nine discs would be required to develop a plow with a working width of 3000 mm. But, in the conventional plow model, this nine-disc implement would be very long (4000 mm). In this way, besides keeping a 3000 mm working width, a plow based on the Tandem system was designed to reduce the length of the plow. As a result, a model consisting of three three-disc plows mounted in parallel (tandem) resulted in a design three times shorter: 1333 mm long. The advantages are that it reduces the effort in the hydraulic lifting of three points (vertical moment, torque), reduces the lateral moment that moves the ground, facilitates the maneuver, and provides more stability to the tractor-plow set. Concurrently with developing the plow, we present the evolution of harrows in text and graphic designs.